Nikon D7200 for dummies - King, Julie Adair (--For dummies., 2015)
Your plain-English, full-color guide to the Nikon D7200 Your Nikon D7200 comes packed with enough power to satisfy even seasoned photographers. Unfortunately, it doesn't come with an easy guide on how to adjust the camera's settings to get the photos you want. That's where Nikon D7200 For Dummies comes in! Brimming with the tips, tricks, and friendly instruction you'd gain in a basic photography course, it shows you how to get the very most out of your new Nikon D7200-without losing your cool. Written by an experienced photographer and photography teacher, this fun, no-nonsense guide quickly gets you up and running on taking your first photos in automatic mode, then moves on to help you grasp more advanced features, like controlling exposure, adjusting color and focus for better results, using scene modes and priority modes, shooting portraits, action shots, outdoor shots, and night images-and so much more.-Navigate your camera's buttons, dials, and settings -Apply pro tricks to get better color, focus, and sharpness from your images -Control exposure settings and jump from auto mode to manual -Make sense of tricky material through full-color explanations of core photography concepts If you're the proud new owner of a Nikon D7200, but don't have a ton-or any-experience with cameras, this hands-on guide will have you taking photos like a pro in no time!